2000
DOI: 10.1097/00008877-200006000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated MK-801-induced motor hyperactivity in rats with the neonatal lesion of the ventral hippocampus

Abstract: Neonatal lesions of the ventral hippocampus in rats produce changes in spontaneous and pharmacologically induced dopamine-dependent behaviors that emerge in early adulthood. Neural mechanisms underlying these changes may have implications for understanding the neurobiology of schizophrenia, putatively a neurodevelopmental disorder. In this study, we evaluated the effects of MK-801 (dizocilpine), on automated measures of distance traveled and stereotypies in adult rats with neonatal (postnatal day 7) lesions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 73 publications
2
50
0
Order By: Relevance
“…The onset of the schizophrenic symptoms typically appears in early adulthood, and the NVH lesion-induced behavioral abnormality in rats also appeared only after puberty (Lipska et al, 1993(Lipska et al, , 1995. Furthermore, in line with the DA and glutamate hypothesis of schizophrenia, NVH-lesioned rats exhibited exacerbated responses to dopamine direct/indirect agonists and NMDA antagonists, suggesting intrinsic dopaminergic and glutamatergic dysfunctions in these rats (Al-Amin et al, 2000;Lipska et al, 1993Lipska et al, , 1995. As schizophrenic patients whose symptoms could be precipitated by stressful life events (Howes et al, 2004), the lesioned rats also exhibited hypersensitivity to stress (Lipska et al, 1993).…”
Section: Introductionmentioning
confidence: 68%
“…The onset of the schizophrenic symptoms typically appears in early adulthood, and the NVH lesion-induced behavioral abnormality in rats also appeared only after puberty (Lipska et al, 1993(Lipska et al, , 1995. Furthermore, in line with the DA and glutamate hypothesis of schizophrenia, NVH-lesioned rats exhibited exacerbated responses to dopamine direct/indirect agonists and NMDA antagonists, suggesting intrinsic dopaminergic and glutamatergic dysfunctions in these rats (Al-Amin et al, 2000;Lipska et al, 1993Lipska et al, , 1995. As schizophrenic patients whose symptoms could be precipitated by stressful life events (Howes et al, 2004), the lesioned rats also exhibited hypersensitivity to stress (Lipska et al, 1993).…”
Section: Introductionmentioning
confidence: 68%
“…It is notable that this limited ablation leads to such a comprehensive spectrum of behavioral abnormalities, and supports the idea that higher brain regions such as the cortex could comprise a primary site of dysfunction in schizophrenia pathogenesis. Consistent with this notion, rats with neonatal hippocampal lesions have also been considered to comprise a rodent schizophrenia model (19,23).…”
Section: Discussionmentioning
confidence: 98%
“…injections. This dose regimen was chosen to emulate the therapeutic range of doses given to patients (Kapur et al, 2000), and was showed to be effective in our previous behavioral and biochemical studies (Al-Amin et al, 2000;Lipska et al, 2001Lipska et al, , 2003. All animals were administered daily injections of drug or vehicle for 4 weeks prior to a single injection of BrdU (200 mg/kg,i.p.).…”
Section: Animals and Drug Administrationmentioning
confidence: 99%